Megaherbivore exclusion led to more complex seagrass canopies and increased biomass and sediment Corg pools in a tropical meadow - Samper-Villarreal, Jimena; Moya-Ramírez, Jairo; Cortés, Jorge (Frontiers in Marine Science, 2022)
In some regions of the Caribbean Sea, seagrasses have been negatively affected by sea turtle overgrazing. Seagrass canopy complexity has declined at a long-term monitoring site in Costa Rica. We deployed megaherbivore exclosures for 13 months and found an increase over time in seagrass cover and maximum canopy height to 75% and 20 cm respectively in the exclosures; while they remained steady in controls at < 25% and 5 cm. Following exclusion, above ground biomass was higher in exclosures (320 ± 58 g DW m-2) compared to controls (171 ± 60 g DW m-2). Leaves were longer and wider in the exclosures (8 ± 5 cm and 0.8 ± 0.2 cm) compared to controls (2 ± 2 cm and 0.5 ± 0.1 cm). Above ground biomass Corg pools in exclosures (1.2 ± 0.2 Mg ha-1) were two-times higher than in controls (0.6 ± 0.2 Mg ha-1). Meanwhile, there was no variation between treatments in seagrass shoot density (1,692 ± 803 shoots m-2), below ground biomass (246 ± 103 g DW m-2) and its Corg pool (0.8 ± 0.4 Mg ha-1). Relative sediment level increased up to 4.4 cm within exclosures revealing a net increase in sediment Corg, while surficial sediment Corg percentage was similar between exclosures and controls. Releasing these meadows from megaherbivore grazing therefore led to a clear increase within exclosures of seagrass cover, canopy complexity, above ground biomass, and Corg pools in above ground biomass and sediment. Our study reveals that the decline in canopy complexity over time at this meadow is linked to megaherbivore grazing and has most likely led to a decrease in blue carbon pools. Excessive megaherbivore grazing at this site could lead to a continued decline or potential loss of the meadow, and seagrass conservation and restoration initiatives should include consideration of trophic dynamics.